2019
DOI: 10.1029/2018jd029076
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electrostatic Charge on the Propagation of GPS (L‐band) Signals Through Volcanic Plumes

Abstract: Recent field studies have shown that the presence of ash in the atmosphere can produce measurable attenuation of Global Positioning System (GPS) signals (Aranzulla et al., 2013, https://doi.org/10.1007/s10291-012-0294-4; Larson, 2013, https://doi.org/10.1002/grl.50556; Larson et al., 2017, https://doi.org/10.1016/j.jvolgeores.2017.04.005). The ability to detect plumes using GPS is appealing because many active volcanoes are already instrumented with high‐quality receivers. However, analyses using a Ralyeigh ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Dusty or complex plasmas, consisting of microscopic particles immersed in a weakly ionized gas, are ubiquitous in the natural universe and play important roles in man-made systems [1][2][3][4][5][6]. When exposed to a plasma environment, particles gain charge by collecting discrete ions and electrons on their surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Dusty or complex plasmas, consisting of microscopic particles immersed in a weakly ionized gas, are ubiquitous in the natural universe and play important roles in man-made systems [1][2][3][4][5][6]. When exposed to a plasma environment, particles gain charge by collecting discrete ions and electrons on their surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, at diameters below 1 mm, the absorption cross-section is significantly increased. This can be seen in Figure 3, which shows the percent difference between the absorption and scattering cross-sections as a function of particle diameter and charge up to the breakdown voltage of 2.7 E-5 C/m 2 , the theoretical maximum charge possible under standard atmospheric conditions (Méndez Harper et al, 2019).…”
Section: Charged Surface Mie Modelmentioning
confidence: 92%
“…The model also did not consider constituents of the plume other than ash, or charging of the ash particles. Charged particles were modeled by Méndez Harper et al (2019), who incorporated a full Mie model (Mie, 1978) of both the absorption and scattering cross-sections. This study found a significant increase in attenuation for smaller particles.…”
Section: Absorption and Scattering From Tephramentioning
confidence: 99%
See 2 more Smart Citations